In-Service Fatigue Reliability of Structures - Petinov, Sergei V. (Solid Mechanics and Its Applications, 2018)
This book provides readers with the latest know-how and tools needed to assess the in-service strength and reliability of welded structures. It addresses the two principal mechanisms of structural material deterioration, fatigue and corrosion, which affect the in-service behavior of structures. In this regard, the primary focus is on fatigue in connection with various structural failure scenarios. Realistic and typical examples of welded structures' design and residual life assessment are used throughout the book in order to show readers the complexity of real-world assessments. The book offers a valuable resource for master's students in mechanical and civil engineering, and for engineers whose work involves fatigue design and in-service inspections of welded structures.